IMPLEMENTASI PROGRAM SEKOLAH RAMAH ANAK DI MADRASAH IBTIDAIYAH NEGERI 7 NGANJUK - Rahmawati, Ziara Sufi (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2026)
ABSTRACT Throughout 2023, namely from January to June 2023, referenced from KPAI data shows that there were 1,600 complaints of violence against children, with as many as 400 cases being sexual cases against children. In fact, quite a lot of these cases of violence were carried out by teachers. The motive is to use punishment wrapped in violence as a method of discipline for students. The Indonesian Ministry of Women's Empowerment and Child Protection plays an important role in following up on the problem of violence against children. The government then issued a Child- Friendly School policy, namely Regulation Number 08 of 2014 concerning the Child- Friendly School Policy which is planned to be strengthened by a Presidential Regulation (Perpres). Based on this background, the researcher asks the following research questions: (1) How is MIN 7 Nganjuk planning to move towards the Child-Friendly School program? (2) How is the implementation of the Child-Friendly School program at MIN 7 Nganjuk? (3) How is the evaluation of the implementation of the Child- Friendly School program at MIN 7 Nganjuk? This research is a research using a qualitative approach and descriptive research type. Data collection techniques use interviews, observations, and documentation. While data analysis techniques include data reduction, data presentation and drawing conclusions. The results of the study, namely: (1) planning for MIN 7 Nganjuk to become a Child-Friendly School did not require much time, because long before the rules and habits had referred to the Child-Friendly School program, so there was no difficulty (2) implementation of Child-Friendly Schools at MIN 7 Nganjuk was already at the MAJU stage and moving towards MAMPU when viewed from the components that were fulfilled (3) evaluation of the implementation of the Child-Friendly School program at MIN 7 Nganjuk was not carried out specifically and routinely, but was discussed together with routine meetings once a month.